Magical pow(d)ers: the resistance capital of subaltern networks in Wade Davis’s the Serpent and the Rainbow - Rischard, Mattius (Frontiers in Human Dynamics, 2025)
Posthuman “borderlands” are represented in literature as diverse repetitions of similar dynamics of power. The postcolonial literature of Haiti presents a unique situation in comparison to the networks of power observed in political economic theory. Colonized people are the central actors in Haiti: they create posthuman entities such as the zombies to reclaim a political agency. Employing network theory to new genres of narrative such as non-fiction accounts and even social science texts, one can begin to map networks of power and counter-power in literature using digital humanities methods that demonstrate the conflicts between colonized communities and the analytical frameworks of mobilized Western anthropology. Moreover, the undead corpse provides a powerful medium for violent social commentary on postcolonial societies’ cultural capital that resists social structures created to ignore or suppress historical counter-narratives. In this case, Caribbean voudoun societies retain a genealogy of traditional African American understandings of the zombie to resist cultural appropriation in Anglo American literature. Ethnographic and sociological approaches have yielded substantial documentation of the religious underpinnings of the Haitian zombie; however Wade Davis’s The Serpent and the Rainbow (1985) was the most scientifically successful and popular narrative. Using methods of network theory applied to literature, an approach to The Serpent and the Rainbow that maps Davis’s relations to academic networks in the United States and local acquaintances in Haiti reveals a religious network powered through brokerage, closure, switching, and programming that perpetuates the mysticism of the zombie as a unique form of social resistance capital.